2023
DOI: 10.1007/s00405-023-07886-1
|View full text |Cite
|
Sign up to set email alerts
|

Training spatial hearing in unilateral cochlear implant users through reaching to sounds in virtual reality

Abstract: Background and Purpose Use of unilateral cochlear implant (UCI) is associated with limited spatial hearing skills. Evidence that training these abilities in UCI user is possible remains limited. In this study, we assessed whether a Spatial training based on hand-reaching to sounds performed in virtual reality improves spatial hearing abilities in UCI users Methods Using a crossover randomized clinical trial, we compared the effects of a Spatial training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Our loudspeakers were placed at the same angular distance on a semicircular horizontal arch, all equally far from the test subject. Valzolgher et al 45 showed that moving an acoustic target closer to and farther from the listener elicits further active behaviors aimed at reaching and grasping the corresponding sound source; these behaviors can be trained to improve the localization performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our loudspeakers were placed at the same angular distance on a semicircular horizontal arch, all equally far from the test subject. Valzolgher et al 45 showed that moving an acoustic target closer to and farther from the listener elicits further active behaviors aimed at reaching and grasping the corresponding sound source; these behaviors can be trained to improve the localization performance.…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the experiment, all participants signed an informed consent document, which had received ethical approval from the national ethics committee in France (Ile de France X, N° ID RCB 2019-A02293-54) and registered as clinical trial (clinicaltrials.gov: NCT04183348). The present work focuses on the data collected in the context of a broader sound localization training protocol during the pre-training session only (full results are published in Valzolgher, Todeschini et al, 2022 ; Valzolgher, Gatel, et al, 2022 ; Valzolgher, Bouzaid, et al, 2023 ; and Alzaher et al, 2023 , for NH, bCI, uCI, and uHL participants, respectively). Although the sample size was determined by the research question of the training studies, it is noteworthy that the sample size in each of the groups matches the numerosity of a previous study that investigated a similar experimental question ( Pavani et al, 2017 , N = 17).…”
Section: Methodsmentioning
confidence: 99%
“…These labels change randomly trial by trial. In the experiment 1 [2], white noise sounds were emitted by a real speaker moved by the experimenter around participants [3][4][5][6][7]. The experimenter was guided to reach each of the predetermined positions by following instruction provided on a monitor.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…The findings showed that this type of interaction with sound sources reduced sound localization errors faster and to a greater extent if compared to a control condition in which participants were asked to name sources' labels to identify them. Interestingly, training efficacy generalized to a different sound localization task and extended also to hearing-impaired people [4][5][6][7]. Yet, this approach is unfeasible for rehabilitation at home, and even in the research practice, it requires a great effort and time on the part of the experimenter to move the speaker.…”
Section: Introductionmentioning
confidence: 99%